CONCEPT OF RESTORATIVE JUSTICE IN THE LAW OF THE REPUBLIC OF INDONESIA NUMBER 11 OF 2012 CONCERNING CHILDRENS CRIMINAL COURT SYSTEM - Sari Lukman, Dwi Ratna Kamala (Jurnal IUS, 2014)
Child is an integral part of human survival and the survival of a nation. The strategic role ofchildren is explicitly stated as those mentioned as the statement that the state guarantees theright of every child to live, grow and develop, and to be protected from violence and discrimination, therefore the best treatment for them should be considered as the best treatment all mankind. Imprisonment provided through the formal criminal justice system does not effectively deter child criminals. That even made the growth and development as well as psychological state of the child be disturbed by the sanctions. Therefore, it is necessary to reform the criminal justice system by applying the concept of restorative justice which, in solving the problem, involve the perpetrators, victims, families perpetrator/victim and other relevant parties to work together to find a fair settlement with emphasis on restoring back to its original state and not retaliation. Philosophical consideration should be based on the best treatment for children, and juridical basis to achieve legal certainty with settings based on justice and expediency to ensure child protection. Diversion is the diversion to remove the criminal justice process into the outside of the criminal justice process. So in any investigation law enforcer shall seek diversion through the application of restorative justice. Diversion mechanism starts from the later stages of investigation and subsequent prosecution and in the trial.Keywords: Children, Restorative Justice and Diversion.